General Principles of Creating a Marked Language Body - Abbosjon Mirzayev (Zien Journals, 2022)
The article discusses the basic principles of corpus linguistics, a new field in applied marked Uzbek linguistics, as well as the process of designing and constructing corpus. Examples of achievements of world linguistics in the creation of corpus resources in the Uzbek language are given. Practical linguistic experience proves how to set up the first stage of corpus linguistics.
Keywords: corpus; marked corpus linguistics; genre-thematic structure; VP Zakharov